Improving the translation of analgesic drugs to the clinic: animal models of neuropathic pain - Percie du Sert, N (BlackWell Publishing Ltd, 2014)
Neuropathic pain remains an area of considerable unmet clinical need. Research based on preclinical animal models has failed to deliver truly novel treatment options, questioning the predictive value of these models. This review addresses the shortcomings of rodent in vivo models commonly used in the field and highlights approaches which could increase their predictivity, including more clinically relevant assays, outcome measures and animal characteristics. The methodological quality of animal studies also needs to be improved. Low internal validity and incomplete reporting lead to a waste of valuable research resources and animal lives, and ultimately prevent an objective assessment of the true predictivity of in vivo models.